Surgical Experience with Burst Liver Abscess Causing Empyema Thoracic and Broncho Pleural Fistula - Rajbhandari, Gambhir Lal (Medical Journal of Shree Birendra Hospital, 2000)
Surgical Experience with Burst Liver Abscess Causing Empyema Thoracic and Broncho Pleural Fistula